PARP inhibitors in testicular germ cell tumors: what we know and what we are looking for - Parola, Sara; Oing, Christoph; Rescigno, Pasquale; Feliciano, Salvatore; Carlino, Francesca; Pompella, Luca; Marretta, Antonella Lucia; De Santo, Irene; Viggiani, Martina; Muratore, Margherita; Facchini, Bianca Arianna; Orefice, Jessica; et al. (Frontiers in Genetics, 2024)
Testicular germ cell tumors (TGCTs), the most common malignancies affecting young men, are characterized by high sensitivity to cisplatin-based chemotherapy, which leads to high cure rates even in metastatic disease. However, approximately 30% of patients with metastatic TGCTs relapse after first-line treatment and those who can be defined as platinum-refractory patients face a very dismal prognosis with only limited chemotherapy-based treatment options and an overall survival of few months. Hence, to understand the mechanisms underlying cisplatin resistance is crucial for developing new treatment strategies. This narrative review explores the potential role of PARP inhibitors (PARPis) in overcoming cisplatin resistance in TGCTs, starting from the rationale of their ability to induce DNA damage in cells with homologous recombination repair (HRR). Thus far, PARPis have failed to show meaningful clinical activity in platinum-refractory TGCT patients, either alone or in combination with chemotherapy. However, few responses to PARPis in TGCTs have been detected in patients with BRCA1/2, ATM or CHEK2 mutations, reinforcing the idea that patients should be optimally selected for tailored treatments in the era of personalized medicine. Future preclinical and clinical research is needed to further investigate the molecular mechanisms of cisplatin resistance and to identify novel therapeutic strategies in resistant/refractory TGCTs patients.